2017
DOI: 10.1007/s10548-017-0595-6
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Slow Waves by EEG Topography and Source Localization: Effects of Sleep Deprivation

Abstract: Slow waves are a salient feature of the electroencephalogram (EEG) during non-rapid eye movement (non-REM) sleep. The aim of this study was to assess the topography of EEG power and the activation of brain structures during slow wave sleep under normal conditions and after sleep deprivation. Sleep EEG recordings during baseline and recovery sleep after 40 h of sustained wakefulness were analyzed (eight healthy young men, 27 channel EEG). Power maps were computed for the first non-REM sleep episode (where sleep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 69 publications
7
26
0
Order By: Relevance
“…Consistent with this, the occipital cortex, relative to other cortical areas, shows the smallest changes in SWA at NREM-REM sleep transitions (De Gennaro et al, 2002;Ferrara and De Gennaro, 2011). The relatively low frequency of occipital REM slow waves (Ͻ2 Hz) is consistent with the recent observation of a lower frequency of occipital NREM slow waves (ϳ1 Hz) relative to anterior areas (Bersagliere et al, 2018).…”
Section: Medial-occipital Slow Wavessupporting
confidence: 85%
“…Consistent with this, the occipital cortex, relative to other cortical areas, shows the smallest changes in SWA at NREM-REM sleep transitions (De Gennaro et al, 2002;Ferrara and De Gennaro, 2011). The relatively low frequency of occipital REM slow waves (Ͻ2 Hz) is consistent with the recent observation of a lower frequency of occipital NREM slow waves (ϳ1 Hz) relative to anterior areas (Bersagliere et al, 2018).…”
Section: Medial-occipital Slow Wavessupporting
confidence: 85%
“…Consistent with this, the occipital cortex, relative to other cortical areas, shows the smallest changes in SWA at NREM-REM sleep transitions [15,77]. The relatively low frequency of occipital REM slow waves (<2 Hz) is in line with the recent observation of a lower frequency of occipital NREM slow waves (~1 Hz) relative to anterior areas [78].…”
Section: Discussionsupporting
confidence: 84%
“…Directly relating our findings to in vitro work or studies using anaesthetized, awake, or immobilized animals recorded out of a dynamic sleep-wake history context might therefore not always be straightforward. We found that the well-known frontal dominance of EEG δ-power increases after SD (Cajochen et al, 1999, Munch et al, 2004, was specific to the δ2 band in both species, whereas δ1 increases were smaller and concerned a larger percentage of the cortex, a finding also observed recently in humans (Bersagliere et al, 2018). This latter observation is consistent with the SO engaging the entire neocortex (Contreras and Steriade, 1995, Massimini et al, 2004, Neske, 2015.…”
Section: Neuronal Substrates Of δ1 and δ2supporting
confidence: 89%